The Wordsworth Dictionary of the Occult - Nataf, Andre (Wordsworth Editions Ltd, 1994)
This book covers the story and the nature of occultism, details the great occult figures of the past- Bacon, Bohme, Hiram, Nostradamus, Paracelsus and Swedenborg.
Keywords: Dictionaries-Reference-Non fiction